A física na visão de Ernst Mach: De uma crítica a Newton às teorias gravitacionais - Gracia, G.b. De (Sociedade Brasileira de Física, 2019)
Abstract The goal of the present article is to introduce the key concepts of the Ernst Mach's philosophy of science as well as to analyze its influence on gravitational theories. In order to do so, we show that it culminates in a criticism about Newton's absolute space idea. The mentioned criticism had considerable influence on Albert Einstein, an enthusiastic follower of Mach's ideas, such that it motivates him to create a theory that encompass great part of its concepts. Finally, we study the Einstein's originals papers in order to analyse the compabitility between his gravitational theory and the E.Mach's ideas. So, we also comment about one generalization that intend to incorporate all the Machian epistemology.

Resumo O presente trabalho possui como objetivo introduzir conceitos chave da filosofia da ciência do físico austríaco Ernst Mach, assim como analisar a sua influência sobre teorias gravitacionais. Para tal, mostraremos que ela culmina numa crítica à ideia de espaço absoluto de Newton. Essa crítica teve considerável influência sobre Albert Einstein, entusiasta da filosofia de Mach, e o motivou a construir uma teoria que englobasse boa parte dos seus conceitos. Finalmente, analisaremos dois dos trabalhos originais de Einstein a fim de analisar a compatibilidade entre sua teoria gravitacional e as ideias de E.Mach. Assim, também comentaremos a respeito de uma generalização de sua teoria que visava incorporar toda a epistemologia Machiana.
The physics in the view of Ernst Mach: From a criticism to Newton to the gravitational theories
Keywords: Philosophy of science; gravitation; Mach's and Einstein's ideas; Filosofia da ciência; gravitação; ideias de Mach e Einstein